Baidu, Weibo and Renren: the global political economy of social media in China. Issue 1 (2nd January 2016) - Fuchs, Christian
Abstract : The task of this work is to conduct a global political-economic analysis of China's major social media platforms in the context of transformations of the Chinese economy. It analyses Chinese social media's commodity and capital form. It compares the political economy of Baidu (search engine), Weibo (microblog) and Renren (social networking site) to the political economy of the US platforms Google (search engine), Twitter (microblog) and Facebook (social networking site) in order to analyse differences and commonalities. The comparative analysis focuses on aspects such as profits, the role of advertising, the boards of directors, shareholders, financial market values, terms of use and usage policies. The analysis is framed by the question to which extent China has a capitalist or socialist economy.